The photoacoustic effect of near-infrared absorbing porphyrin derivatives prepared via click chemistry. (January 2018) - Li, Liaoliao; Wang, Dong; Wang, Lei; Ramella, Daniele; Wang, Hao; Gao, Hong; Zhang, Jingjing; Xing, Yan; Li, Bingnan; Yang, Zhou; Cao, Hui; He, Wanli
Abstract: A great demand of near-infrared (NIR) light-absorbing agents has recently arisen, as they are employed to enhance photoacoustic (PA) imaging and photothermal therapy (PTT) technologies. In this study, applications of a series of NIR absorbing porphyrin derivatives to PA and PT were carefully examined. Among other interesting results, it was found that the click reagent F4 -TCNQ showed a higher PA intensity than those of TCNE and TCNQ. Moreover, the PA intensity remained high when R33 was dispersed in water. The toxicity of R33 molecules embedded into hydrophobic phospholipid bilayer of liposomes (R33⊂L) was low. Systematic research of the NIR dyes not only allowed for a more educated design of NIR absorbing dyes for PA signal enhancement, but also provided us with a way to reduce the solution toxicity of oil soluble organic NIR dyes. Highlights: The PA and PT effects of a series of NIR absorbing porphyrin derivatives are characterized and the click reagent F4 -TCNQ can effectively lead to the higher PA intensity. Different solvents may have an effect on the PA intensity of NIR absorbing porphyrin derivatives.